Rainfall parameterization in an off-line chemical transport model - Giannakopoulos, Christos; Good, P.; Law, K. S.; Wang, K. Y.; Akylas, Evangelos; Koussis, A.D. (My University, 2004)
In this paper, techniques for the modelling of both large-scale and convective precipitation in a three-dimensional off-line chemical transport model are proposed. Relatively simple formulations are proposed that will yield meaningful rainfall rates to be used for the wet deposition of chemical species without compromising the computational efficiency of the model. As the profiles of humidity and temperature obtained from available meteorological analyses are too stable to produce any rainfall, we destabilize them through advection. This technique has been tested here for the large-scale rainfall only, but can also be applied to the convective rainfall to make it less spotty and improve the comparison with observations. For an off-line model, TOMCAT seems to capture surprisingly well the global distribution pattern of the rainfall as witnessed by observational climatologies. It performs well in capturing the dry subtropical regions and the wet Asian monsoon season as well as the mitigation of rains in the tropics with the change of season. However, it underestimates precipitation in the continents in the summer and south of 30 °S all year round. These shortcomings could be improved if we apply the advection technique to the convective rainfall as well. In addition, we could obtain the surface precipitation totals from the meteorological analyses and subsequently scale these amounts vertically using our model-derived grid point condensation rate. Copyright © 2004 Royal Meteorological Society.
Keywords: Atmospheric composition and structure; Meteorology and atmospheric dynamics